Moral Values in Rachel Platten’s Selected Songs Lyric - Asroriyah, Atik Muhimatun; Mitsalina, Endah; Pratiwi, Berlin Insan; Lestari, Sri (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
In the song, of course, there is a deep meaning from the songwriter. Lyrics as one of the elements of the song, it contains an outpouring of personal feelings and a series of words that are often influenced by the values ??of a culture, social, or moral. This study seeks to examine and describe the moral values ??contained in the song lyrics of Rachel Platten. This study aims to describe the types and characteristics of the moral values ??of the songs “Fight Song”, “Stand by You”, “Broken Glass”, and “Soldiers”. The method used in this research is qualitative method. The data in this study are verbal in the form of words, phrases or sentences contained in the lyrics of songs by Rachel Platten, which are adapted to the purpose of the study. The next step is data collection. It’s the procedure of collecting and measuring. Also, the procedure of analyzing accurate insights for research using standard validated techniques. Data analysis includes data reduction, data presentation, and conclusion drawing and data verification. The results showed that in the lyrics of the songs are kinds and characteristics of moral value. Keywords: Characteristics of Moral Value, Kinds of Moral Value, Rachel Platten, Songs Lyric